PP.41.26: DIFFERENT PERIODS OF HIGH-FAT DIET PRODUCE HYPERTENSION AND VASCULAR PROSTANOID ALTERATION IN THE RAT. (June 2015) - Puyó, A.; Lee, H.J.; Sánchez Eluchans, N.M.; Merlo, J.S.; Cantú, S.M.; Donoso, A.S.; Peredo, H.A.
Abstract : Objective: A high-fat (HF) diet produces in the rat insulin resistance which is related to cardiovascular alterations such as hypertension. Prostanoids (PR), cyclooxygenase-derived arachidonic acid metabolites, have vasoactive properties and mediate inflammation. The aim of this study was to analyze the effect of different periods of HF diet on blood pressure (BP), metabolic parameters, hepatic morphology and mesenteric vascular bed PR production in male Sprague-Dawley rats. Design and method: Four groups were studied during 8 and 12 weeks of HF diet (n = 4 each): Control (C8 and C12), standard diet (SD) and tap water to drink; HF diet (HF8 and HF12), 50% (w/w) bovine fat added to SD and tap water. PR were determined by HPLC and hepatic morphometry by image analysis performed by means of Micrometrics software. Results: HF diet increased liver weight after 12 weeks of treatment (g, HF12, 13.3 ± 0.7 vs. C12, 11.1 ± 0.8, p < 0.05); meanwhile, % fat liver (HF8, 65 ± 18 vs. C8, 5 ± 3, and HF12, 60 ± 16 vs. C12, 0.8 ± 0.3, p < 0.05); glycemia (mg/dl, HF8, 149 ± 3 vs. C8, 112 ± 9 and HF12, 141 ± 9 vs. C12, 127 ± 7, p < 0.05); insulinemia (ng/dl, HF8, 3.5 ± 0.5 vs. C8, 1.6 ± 0.2 and HF12, 3.4 ± 0.6 vs. C12, 1.1 ± 0.2, p < 0.05); triglyceridemia (mg/dl, HF8, 110 ± 6 vs. C8, 62 ± 11 and HF12, 177 ± 45 vs. C12, 91 ± 18, p < 0, 05) and systolic BP (mmHg, HF8, 150 ± 9 vs. C8, 125 ± 1 and HF12, 149 ± 3 vs. C12, 121 ± 6, p < 0, 01) were elevated in both periods of treatment. On the other hand, HF diet increased the release of the vasoconstrictor PR thromboxane (TX) B2, stable metabolite of TXA2, (ng PR/mg of tissue, HF8 117 ± 10 vs. C8, 72 ± 7 and HF12, 123 ± 12 vs. C12, 71 ± 6, p < 0, 05); and prostaglandin (PG) F2alpha (ng/mg, HF8, 154 ± 15 vs. C8, 93 ± 5 and HF12, 160 ± 13 vs. C12, 87 ± 9, p < 0, 05) in both periods. The release of vasodilator PRs prostacyclin and PGE2 was not altered by the treatment. Conclusions: In conclusion, the increase in systolic BP induced by HF diet since the 8th week of the dietary modification could be attributed, at least in part, to the elevated production of vasoconstrictor PRs in a resistance vascular bed such as the mesenteric.